Trade reforms and industry wage premium: Evidence from Argentina - Guillermo Falcone; Luciana Galeano (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2017)
This paper studies the impact of Argentina trade liberalization during the nineties on the industry wage premium structure. We find that accounting for unobserved time invariant industry characteristics is crucial. When we do not control for industry fixed effects, we find that workers in protected sectors receive lower wages. However, introducing industry fixed effects reverses the results; tariff protection creates sector specific rents that are in part translated to workers in terms of greater wages. Since Argentina's tariff structure during this period protected relatively more sectors employing higher proportions of skilled workers, nineties trade policy may have had an adverse effect on Argentina's income distribution.
Keywords: 330; skill premium; industry premium; trade liberalization; Argentina